Millennials’ travel motivations and desired activities within destinations - Rita, Paulo (2022)
Rita, P., Brochado, A., & Dimova, L. (2019). Millennials’ travel motivations and desired activities within destinations: a comparative study of the US and the UK. Current Issues in Tourism, 22(16), 2034-2050. https://doi.org/10.1080/13683500.2018.1439902